2009
DOI: 10.1016/j.ijid.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Non-typhoidal Salmonella septic arthritis in an immunocompetent child with a pharyngeal streptococcal infection

Abstract: We report the case of an immunocompetent child who showed monoarticular arthritis and fever, preceded by pharyngitis and arthralgias. Because group A beta-hemolytic Streptococcus had been detected in the pharyngeal swab, erythromycin was given on admission. However, based on ultrasound examination, therapy with ceftriaxone and joint fluid drainage were promptly performed, and a rapid and full recovery followed. Meanwhile, Salmonella enterica infection was revealed in blood and joint fluid. Our case suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Contrary to previous S. typhimurium epidemic in Italy and other countries, the symptomatology was frequently severe in many children aged less than two years, and required hospitalization for rehydration and intravenous antibiotic therapy [ 1 , 7 ]. A five-year old boy also had a concomitant hip joint arthritis, which can occasionally occur during S. enterica infection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to previous S. typhimurium epidemic in Italy and other countries, the symptomatology was frequently severe in many children aged less than two years, and required hospitalization for rehydration and intravenous antibiotic therapy [ 1 , 7 ]. A five-year old boy also had a concomitant hip joint arthritis, which can occasionally occur during S. enterica infection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our case presents a unique cause of shoulder pain in an otherwise healthy adolescent female athlete which highlights the importance of maintaining a broad differential diagnosis when evaluating acute musculoskeletal pain, especially when the pain is disproportional to the history. Our particular case highlights an unusual location and causative organism, S. infantis , for septic arthritis in an immunocompetent patient, which has not been well documented in the literature (1,23). In addition, the suspected seeding from the bacterial gastroenteritis also is very rare.…”
Section: Discussionmentioning
confidence: 78%
“…7 Several studies have suggested the occurrence of elevated virulence and invasiveness of S. enterica and subspecies enterica Serovar Enteritidis and Typhimurium isolates. 1 Clinically, it is very difficult to differentiate between septic arthritis in its early stage from arthritis associated with underlying SLE delaying diagnosis. CRP levels in SLE patients are raised during exacerbations but studies have shown that a level greater than 50mg/L strongly suggests infection.…”
Section: Discussionmentioning
confidence: 99%
“…Septic arthritis is a rare consequence of salmonella bacteraemia noted in <1% of cases reported in the literature in patients with an underlying disease such as sickle cell disease or systemic lupus erythematosus (SLE). 1,2 Patients with SLE have an increased incidence of bacterial infections due to hypocomplementaemia, phagocyte defect, cellular defect and use of immunosuppressants and cytotoxic medications as therapy. 3 The infections most commonly involve the lungs, skin and genitourinary tract.…”
Section: Introductionmentioning
confidence: 99%